2008
DOI: 10.1029/2008jd009904
|View full text |Cite
|
Sign up to set email alerts
|

Radiative properties of aerosol mixture observed during the dry season 2006 over M'Bour, Senegal (African Monsoon Multidisciplinary Analysis campaign)

Abstract: [1] During the dry season in the Western Africa region the outbreaks of biomass burning aerosols occur on a background of frequent dust storms. In the frame of the African Monsoon Multidisciplinary Analysis (AMMA) campaign we studied optical properties and radiative effects of aerosol mixture and dust observed from January to March 2006 over M'Bour, Senegal. The aerosol burden during the observing period was notably below the average of previous years. However, variability of aerosol sizes and spectral absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
105
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 51 publications
11
105
2
Order By: Relevance
“…Two different zones appear, with a first one (16 Slingo et al (2006) who indicated that reflected fluxes at the TOA rose by 100 W/m 2 at Niamey. Our simulation for 10 March over Senegal is also in agreement with the instantaneous TOA forcing calculated by Derimian et al (2008) in M'Bour, which range from about −70 to −90 W/m 2 (at noon). In addition, Milton et al (2008) reported values comprised between −10 and −80 W/m 2 over the Sahel region.…”
Section: Solar Spectral Rangesupporting
confidence: 76%
See 1 more Smart Citation
“…Two different zones appear, with a first one (16 Slingo et al (2006) who indicated that reflected fluxes at the TOA rose by 100 W/m 2 at Niamey. Our simulation for 10 March over Senegal is also in agreement with the instantaneous TOA forcing calculated by Derimian et al (2008) in M'Bour, which range from about −70 to −90 W/m 2 (at noon). In addition, Milton et al (2008) reported values comprised between −10 and −80 W/m 2 over the Sahel region.…”
Section: Solar Spectral Rangesupporting
confidence: 76%
“…Milton et al (2008) modelled that dust particles considerably reduce net downward shortwave flux at the surface over a large part of West Africa with maximum of 200 W/m 2 . In addition, in the framework of the AMMA program, Derimian et al (2008) estimated the aerosol surface radiative forcing over M'Bour, Senegal. The estimations were based on the aerosol properties derived from AERONET retrievals and validated against broad-band radiation measurements conducted during AMMA campaign period at M'Bour observational site.…”
Section: Solar Spectral Rangementioning
confidence: 99%
“…In the frame of the AMMA experiment, all the instruments have been installed at the geophysical station of the Institut de Recherche pour le Développement (IRD center) in M'Bour, 80 km south of Dakar (Derimian et al, 2008). The site is located close to the sea shore and is affected by the sea breeze and the advection of maritime aerosols in the boundary layer.…”
Section: Instrumentation and Methodologymentioning
confidence: 99%
“…Four AMMA super stations have been selected for a comprehensive investigation of aerosol properties, along with radiation measurements (Banizoumbou -Niger, Djougou -Benin, Tamanrasset -Algeria, and M'Bour -Senegal). The M'Bour site is located in an area where the contribution of biomass burning aerosol is expected to be significant, in addition to mineral dust influence Derimian et al, 2008). A special observing period has been established for the dry season (SOP0, January-February 2006), with a focus on aerosol chemical, physical, and optical properties and the associated radiative effects Chou et al, 2008;Derimian et al, 2008;Pelon et al, 2008;Rajot et al, 2008;Heese and Wiegner, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation